A Glutathione-Protected Gold-Copper Nanoclusters and Ce 3+ Fluorescent probes forming assemblies and their applications

By using gold-copper nanoclusters based on glutathione protection and Ce3+ assembly as fluorescent probes, the problem of complex and cost of detection methods in the prior art is solved, and a high sensitivity, fast and accurate detection method is achieved. Testing for metals.

CN114563385BActive Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210214762.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-07
Publication Date
2025-02-14
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

The prior art lacks a simple, fast, reliable, accurate and reproducible analysis method, and the traditional detection method is cumbersome to operate and has high equipment cost, making it difficult to use for rapid detection.

Method used

The gold-copper nanocluster based on glutathione protection and Ce3+ formed as a fluorescent probe, and high-sensitivity quantitative detection is achieved through its interaction with bayberry.

Benefits of technology

It achieves high sensitivity, rapid and accurate detection of bayberry sulfin, has good reproducibility and low detection limit, and has high selectivity for bayberry sulfin, which can effectively distinguish other flavonol derivatives and amino acids with similar structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114563385B_ABST
    Figure CN114563385B_ABST
Patent Text Reader

Abstract

A Glutathione-protected Gold-Copper Nanocluster and Ce 3+ The fluorescent probe (AuCuNCs‑Ce 3+ ) and its application in myricetin detection, belonging to the field of fluorescent probe technology. The present invention uses CuSO4·5H2O and HAuCl4·3H2O as Cu and Au sources, and glutathione as a reducing agent and stabilizer to prepare a fluorescent probe. AuCuNCs‑Ce 3+ It has good recognition selectivity and anti-interference ability for myricetin; response mechanism research shows that AuCuNCs‑Ce 3+ The fluorescence quenching response of the assembly to myricetin is static quenching, which is mainly caused by the inner filter effect. The probe has the advantages of fast response speed, wide response range (0-300 μM), high selectivity and sensitivity for the detection of myricetin. It shows good linearity in the concentration range of 1.0-7.0 μM, and the detection limit is 0.14 μM.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fluorescent probes, and particularly relates to a method for preparing a fluorescent probe based on glutathione-protected gold-copper nanoclusters and Ce 3+ The assembled AuCuNCs-Ce 3+ ) and its application as a reagent in the detection of myricetin. Background Art

[0002] Myricetin (Myricetin, molecular formula C 15 H 10 O 8 , molecular weight 318.24; CAS number: 529-44-2) is a flavonoid compound that is widely found in many natural plants and daily foods such as Myricetaceae, Grapeaceae, Leguminosae, berries, fruits, vegetables, honey, red wine, tea, etc. Modern pharmacological studies have shown that myricetin has multiple biological functions such as anti-inflammatory, anti-tumor, antibacterial, antiviral, and anti-obesity. In addition, myricetin can be used in cosmetics to regulate UVB-induced H 2 O 2 The production of myricetin can inhibit the production of photoaging free radicals in the skin. Although myricetin is widely distributed and beneficial to human health, there are still few fluorescence detection methods. Therefore, it is of great application value to establish a simple, rapid, reliable, accurate and reproducible method for the analysis of myricetin.

[0003] The main analytical methods for the traditional detection of myricetin include electrochemical method and high performance liquid chromatography. Although this method has good precision and low detection limit, it is cumbersome to operate, has high equipment cost, and is difficult to use for rapid detection. With the rapid development of nanomaterials, the use of nanomaterials as fluorescent probes for detection has become one of the research hotspots. Among them, fluorescent probe technology has attracted much attention due to its high sensitivity, rapidity, and simple operation, and is considered to be an effective means of detecting trace substances. The fluorescent probes currently used are mainly quantum dots and metal nanoclusters. Although other fluorescent materials can also be used as optical probes, metal nanoclusters have unique optical properties and have been widely used in biosensing, bioimaging, new catalysts and other fields in recent years. In addition, thanks to the great progress in the synthesis of metal nanoclusters, copper nanoclusters with customized size, good stability and good quality can be easily obtained. Copper nanoclusters have the characteristics of high luminescence efficiency, long fluorescence lifetime, good optical and chemical stability, and large Stokes shift. Recently, they have received more and more attention and have been widely used in optical sensing and bioimaging.

[0004] Copper nanoclusters are easily oxidized, resulting in poor stability and limited application, so their fluorescence properties need to be improved. According to literature reports, doping with other metal atoms can greatly improve the photoluminescence performance and stability of metal nanoclusters. Therefore, the present invention uses gold atoms to dope copper nanoclusters to form gold-copper bimetallic nanoclusters, and their stability is greatly improved. In particular, the nanoclusters have excellent aggregation-induced emission (AIE) properties. 3+ Assembled to form aggregates (AuCuNC-Ce 3+ ) can greatly improve the photoluminescence performance and storage time of the bimetallic nanocluster. The present invention further uses the assembly as a fluorescent probe to achieve high-sensitivity quantitative detection of myricetin. Summary of the invention

[0005] The purpose of the present invention is to provide a glutathione-protected gold-copper nanoclusters and Ce 3+ The fluorescent probe formed by the assembly and its application in detecting myricetin. The fluorescent probe is a combination of gold-copper nanoclusters and Ce 3+ The assembly formed by the interaction is used to detect myricetin.

[0006] Firstly, copper nanoclusters ( Figure 1 a), due to its poor stability ( Figure 1 b), which is not conducive to later applications and needs further optimization and improvement. 4 ·3H 2 O formed gold-copper bimetallic nanoclusters, whose storage time was stable from four days to one week ( Figure 2 b). This indicates that doping with heterogeneous metal atoms provides a new idea to improve the stability of copper nanoclusters. Since the fluorescence intensity of gold-copper nanoclusters is weak, the aggregation-induced emission of metal nanoclusters is a simple and effective method to improve the photoluminescence performance of metal nanoclusters; therefore, the introduction of metal ions Ce 3+ , which significantly enhanced the fluorescence intensity of AuCu nanoclusters ( Figure 4 ), and the fluorescence quantum yield increased to 22%. In addition, the nanoclusters can be stable for 25 days ( Figure 5 ). Therefore, AuCuNCs-Ce 3+ The assembly can serve as a stable fluorescent probe.

[0007] The present invention applies the fluorescent probe to the detection of myricetin, which has the advantages of rapid response ( Figure 6 ), wide response range 0~300μM( Figure 7 ) and exhibited good linearity in the concentration range of 1.0 to 7.0 μM, with a detection limit of 0.14 μM ( Figure 8). In addition, the probe is more selective for myricetin than other flavonol derivatives with similar structures and common amino acids ( Fig. 9 ), and these amino acids and other substances did not interfere with the detection of myricetin ( Fig.10 ), so the probe can effectively detect myricetin. Mechanistic studies show that myricetin makes AuCuNCs-Ce 3+ The quenching mechanism of the assembly can be attributed to the static quenching process (Table 1) and the inner filter effect ( Fig.11 ).

[0008] The present invention discloses a glutathione-protected gold-copper nanocluster and Ce 3+ The fluorescent probe solution that forms the assembly is CuSO 4 ·5H 2 O and HAuCl 4 ·3H 2 O as Cu and Au sources, glutathione (GSH) as a reducing agent and stabilizer; it is prepared by the method described in the following steps:

[0009] (1) First, add 5.0 mL of 160-170 mM glutathione aqueous solution to 5.0 mL of 8-12 mM CuSO 4 ·5H 2 O aqueous solution, after the solution becomes a white suspension, add 1.0M NaOH aqueous solution dropwise until the turbid solution becomes transparent again and the solution is light yellow. At this time, the pH of the solution is 4.0-5.0, and then stir at room temperature for 1.5-3.0h to obtain a copper nanocluster solution;

[0010] (2) HAuCl 4 ·3H 2 O is added to the copper nanocluster solution obtained in step (1) and stirred for 2 to 4 hours. 4 ·3H 2 The final concentration of O was 1.0-1.5 mM to obtain a gold-copper nanocluster solution;

[0011] (3) adding 15 to 30 mL of ethanol to the gold-copper nanocluster solution obtained in step (2), and then centrifuging at 6000 to 8000 rpm for 10 to 20 minutes to collect the precipitate; dissolving the precipitate in distilled water, adding ethanol and centrifuging 3 to 5 times to remove all residual small molecules, and freeze-drying to obtain pure gold-copper nanocluster powder;

[0012] (4) The pure gold-copper nanocluster powder obtained in step (3) was placed in a 10 mM HEPES-NaOH buffer solution with a pH of 6.5 to 7.0 to prepare a gold-copper nanocluster concentration of 0.4 to 0.6 mg·L -1Then, a cerium nitrate aqueous solution is added thereto for 10 to 30 minutes, and the final concentration of the cerium nitrate is 100 to 300 μM, thereby obtaining a glutathione-protected gold-copper nanocluster and Ce nanocluster according to the present invention. 3+ The assembled AuCuNCs-Ce 3+ ) of the fluorescent probe solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 : (a) Fluorescence emission spectrum of CuNCs, (b) stability curve of CuNCs.

[0014] Figure 2 :(a) Different contents of HAuCl 4 ·3H 2 O Fluorescence emission spectra of AuCuNCs solutions, (b) different contents of HAuCl 4 ·3H 2 Stability curve of AuCuNCs solution.

[0015] Figure 3 :(a) Excitation emission spectrum of AuCuNCs, (b) Transmission electron microscopy of AuCuNCs, (c) Particle size distribution of AuCuNCs, (d) Infrared absorption spectrum of AuCuNCs, (e) Photoelectron spectrum of copper element in AuCuNCs, (f) Photoelectron spectrum of gold element in AuCuNCs.

[0016] Figure 4 :(a) Different Ce 3+ Concentration of AuCuNCs-Ce 3+ Fluorescence emission spectra of the solution, (b) AuCuNCs-Ce 3+ The fluorescence intensity of the solution at 590 nm is similar to that of Ce 3+ Concentration relationship curve.

[0017] Figure 5 :AuCuNCs-Ce 3+ Fluorescence intensity stability curve of the solution at 590nm.

[0018] Figure 6 :AuCuNCs-Ce 3+ Time spectrum of the fluorescence intensity of the solution at 590nm in response to the addition time of myricetin.

[0019] Figure 7 :(a) AuCuNCs-Ce 3+ Response fluorescence spectra of myricetin at different concentrations (0-300 μM), (b) Relationship curve between fluorescence intensity at 590 nm and myricetin concentration in (a).

[0020] Figure 8 :(a) AuCuNCs-Ce 3+ (b) The fluorescence spectrum of the response to low concentration (0-7 μM) of myricetin, and (a) the relationship between the fluorescence intensity at 590 nm and the myricetin concentration.

[0021] Fig. 9 :AuCuNCs-Ce 3+ Fluorescence intensity changes of myricetin and interfering substances.

[0022] Fig.10 :AuCuNCs-Ce 3+ Graph showing the change in fluorescence intensity after mixing myricetin and interfering substances.

[0023] Fig.11 :AuCuNCs-Ce 3+ Fluorescence excitation spectrum of and UV-visible absorption spectrum of myricetin.

[0024] Table 1: AuCuNCs-Ce 3+ Life span change data before and after adding myricetin

[0025]

[0026] Figure 1 Corresponding to Example 1; Figure 2 Corresponding to Example 2; Figure 3 Corresponding to Example 3; Figure 4 Corresponding to Example 4; Figure 5 Corresponding to Example 5; Figure 6 to Figure 8 Corresponding to Example 6; Figure 9-10 Corresponding to Example 7; Fig.11 , Table 1 corresponds to Example 8.

[0027] The excitation wavelength of the gold-copper nanoclusters is 350nm, and the emission wavelength is 606nm ( Figure 3 a). Transmission electron microscopy (TEM) was used to characterize the surface morphology and size of the gold-copper nanoclusters. The nanoclusters were highly dispersed and had a relatively uniform particle size ( Figure 3 b), the average particle size is ~2.8nm ( Figure 3 c) In the infrared spectrum, the typical stretching vibration of SH of GSH is at 2525 cm -1 In the Au-Cu nanoclusters, this peak disappears, indicating that Cu-S and / or Au-S bonds are formed on the metal surface ( Figure 3 d), indicating that the bimetallic nanoclusters were successfully obtained. In addition, in the XPS results, there are two obvious peaks at 932.3eV and 952.2eV, which belong to the Cu 2p of Cu(0) and Cu(I), respectively. 3 / 2and Cu 2p 1 / 2 ( Figure 3 e), the absence of the characteristic peak at 942.0 eV excludes the presence of Cu(II). 7 / 2 and 4f 5 / 2 The characteristic binding energies of Au 4f are 84.1 and 87.7 eV, respectively. 7 / 2 After peak separation, there are two peaks at 83.8 and 84.8 eV, which belong to Au(0) and Au(I) respectively. Figure 3 f). According to the results, it was shown that most of Au(III) was reduced to Au(0) and Au(I) and combined with copper atoms to form gold-copper hybrid nanoclusters. Therefore, gold-copper nanoclusters were successfully prepared, in which Cu(0) and Au(0) formed the metal core and Cu(I) and Au(I) covered the core surface.

[0028] like Figure 4-5 As shown, as different concentrations of Ce were gradually added to the Au-Cu nanocluster solution 3+ , the fluorescence intensity of AuCu nanoclusters was enhanced, and the fluorescence emission wavelength was blue-shifted to 590 nm. 3+ When the concentration reaches 200μM, the saturation Figure 4 ). Therefore, AuCu nanoclusters were mixed with 200 μM Ce 3+ The assembly can be stored for 25 days. Figure 5 ), so AuCuNCs-Ce 3+ As a more stable fluorescent probe.

[0029] like Figure 6-8 As shown, AuCuNCs-Ce 3+ 50 μM myricetin was added to the assembly, and fluorescence spectroscopy was used to observe that myricetin caused AuCuNCs-Ce 3+ The assembly is quenched and responds quickly ( Figure 6 The first 8 minutes or so is the stable time of AuCuNCs-Ce3+ assembly. At the 8th minute, 50 μM myricetin was added, which immediately quenched the assembly. The quenching was stabilized to the intensity that should be quenched by 50 μM myricetin in 2 to 3 minutes. In addition, with the increase of myricetin concentration, the fluorescence intensity of the fluorescent probe at 590 nm decreased, and finally reached saturation when the myricetin concentration was 300 μM. Therefore, the response range of myricetin was 0 to 300 μM ( Figure 7 ), and showed good linearity in the concentration range of 1.0 to 7.0 μM, with a detection limit of 0.14 μM ( Figure 8 ).

[0030] In addition, AuCuNCs-Ce 3+The effects of other substances such as apigenin, quercetin, morin solution and 20 natural amino acid solutions were studied. The results showed that apigenin, quercetin and morin had poorer fluorescence quenching effect than myricetin, and other substances had no effect on the fluorescence quenching of AuCuNCs-Ce 3+ The assembly has an effect ( Fig. 9 ). This indicates that the fluorescent probe can effectively detect myricetin. In addition, 20 natural amino acid solutions were used to test the AuCuNCs-Ce 3+ The interference of these amino acids on the fluorescent AuCuNCs-Ce 3+ The probe detected myricetin with no effect ( Fig.10 ), indicating that this method is an effective means to detect myricetin in practical applications.

[0031] In the process of mechanism study, AuCuNCs-Ce 3+ The average fluorescence lifetime of the assembly before and after the addition of myricetin remained basically unchanged (Table 1), indicating that myricetin has an important effect on the AuCuNCs-Ce 3+ The assembly exhibits a static quenching effect. The maximum absorption peak of myricetin is consistent with that of AuCuNCs-Ce 3+ The excitation spectra of the assemblies overlap ( Fig.11 ), therefore, myricetin makes AuCuNCs-Ce 3+ The quenching mechanism of the assembly may be the inner filter effect. The overall results show that AuCuNCs-Ce 3+ The fluorescence quenching of the assembly can be attributed to the inner filter effect and is a static quenching process. DETAILED DESCRIPTION

[0032] Chloroauric acid trihydrate (HAuCl 4 ·3H 2 O,>99.9%) and copper sulfate pentahydrate (CuSO 4 ·5H 2 O, >99.9%) was supplied by Beijing Chemical Plant (Beijing, China). 4-(2-Hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES, >99.9%), glutathione (GSH) and 20 natural amino acids (Val, Met, Cys, Ile, Pro, Arg, Phe, Gly, Gln, Glu, Thr, Trp, Ser, Ala, Asp, Lys, Leu, Asn, Tyr, His) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai, China). Myricetin, morin, apigenin and quercetin were purchased from Shanghai McLean Biochemical Technology Co., Ltd., and sodium hydroxide (NaOH) was purchased from Sinopharm Chemical Reagent Co., Ltd. All chemicals were analytical grade and were not further purified. Ultrapure water was used throughout the experiments.

[0033] Embodiment 1:

[0034] Add 5.0 mL (163 mM) glutathione aqueous solution to 5.0 mL CuSO 4 ·5H 2 O (10mM) aqueous solution. After the solution becomes a white suspension, 1.0M NaOH solution is added dropwise until the turbid solution becomes transparent again and presents a light yellow color. At this time, the pH of the solution is 4.2. The solution is stirred at room temperature for 2h to obtain a copper nanocluster solution. Fluorescence spectroscopy is used to test the excitation emission of copper nanoclusters (CuNCs) and monitor their stability.

[0035] The results show that the emission of copper nanoclusters is 630nm and the excitation is 350nm ( Figure 1 a), which is basically consistent with the reported copper nanoclusters, but in order to obtain the full spectrum as much as possible, 370nm light excitation was used, and the subsequent fluorescence test uniformly used an excitation wavelength of 370nm. In addition, the copper nanoclusters can only be stable for four days ( Figure 1 b).

[0036] Embodiment 2:

[0037] Based on the copper nanocluster solution in Example 1, HAuCl was doped into the solution at final concentrations of 0.25, 0.50, 0.75, 1.0, 1.25, and 1.5 mM, respectively. 4 ·3H 2 O and continued stirring for 3 hours to obtain a gold-copper nanocluster (AuCuNCs) solution. Fluorescence spectroscopy was used to monitor the emission wavelength and fluorescence intensity changes of the gold-copper nanocluster, and the stability of the gold-copper nanocluster was also monitored.

[0038] The results showed that with the increase of HAuCl 4 ·3H 2 With the increase of O doping concentration, the emission wavelength blue-shifted and the fluorescence intensity decreased slightly. At the same time, when the HAuCl doping concentration was 0.25, 0.50, and 0.75 mM 4 ·3H 2 O, the stability of the AuCu nanocluster solution did not improve; when doped with 1.0, 1.25, and 1.5 mM HAuCl 4 ·3H 2 O, the AuCu nanocluster solution can be basically stable for 7 days ( Figure 2 ), so the doping content is selected to be 1.0-1.5 mM HAuCl 4 ·3H 2 O is the preferred embodiment, and the doping content is selected to be 1.0 mM HAuCl 4 ·3H 2 O as the best implementation.

[0039] Embodiment 3:

[0040] Based on Example 1-2, 5.0 mL (50 mg / mL) of glutathione aqueous solution was added to 5.0 mL of CuSO 4 ·5H 2 O (10 mM) aqueous solution, after the solution becomes a white suspension, add 1.0 M NaOH solution dropwise until the turbid solution becomes transparent again and presents a light yellow color, and stir at room temperature for 2 h. At this time, the pH of the solution is 4.2, and a copper nanocluster solution is obtained. Then, HAuCl with a final concentration of 1.0 mM is added 4 ·3H 2 O to the copper nanocluster solution and stirred for 3 hours. Finally, 20 mL of ethanol was added to the reaction system and the precipitate was collected after centrifugation at 7000 rpm for 15 minutes. The precipitate was dissolved in distilled water, and then ethanol was added and centrifuged 3 times to remove all residual small molecules. Pure gold-copper nanocluster powder was obtained after freeze drying in a freeze dryer and stored at 4 °C for further use.

[0041] The results show that the excitation wavelength of the gold-copper nanoclusters obtained in Example 3 is 350nm, and the emission wavelength is 606nm ( Figure 3 a). Transmission electron microscopy (TEM) was used to characterize the surface morphology and size of the gold-copper nanoclusters. It can be seen from the figure that the nanoparticles have high dispersion and relatively uniform particle size ( Figure 3 b). A systematic analysis of approximately 200 particles revealed an average grain size of ~2.8 nm ( Figure 3 c). Then, infrared spectroscopy was used to monitor the vibration absorption changes of glutathione (GSH) and the ligand GSH in the gold-copper nanoclusters. The typical stretching vibration of SH of GSH appears at 2525 cm -1 , but disappeared in Cu nanoclusters and Au-Cu nanoclusters, indicating that Cu-S and / or Au-S bonds were formed on the metal surface ( Figure 3 d). The results show that bimetallic nanoclusters were successfully obtained. In addition, XPS measurements were performed to determine the valence states of Cu and Au atoms in the bimetallic nanoclusters. There are two obvious peaks at 932.3 eV and 952.2 eV, which belong to the Cu 2p of Cu(0) and Cu(I), respectively. 3 / 2 and Cu 2p 1 / 2 ( Figure 3 e), the absence of the characteristic peak at 942.0 eV excludes the presence of Cu(II). 7 / 2 and 4f 5 / 2 The characteristic binding energies of Au 4f are 84.1 and 87.7 eV, respectively. 7 / 2After peak separation, there are two peaks at 83.8 and 84.8 eV, which belong to Au(0) and Au(I) respectively. Figure 3 f). According to the results, most of Au(III) was reduced to Au(0) and Au(I), and combined with copper atoms to form gold-copper hybrid nanoclusters. Therefore, this example successfully prepared gold-copper nanoclusters, in which Cu(0) and Au(0) formed a metal core, and Cu(I) and Au(I) covered the core surface.

[0042] Embodiment 4:

[0043] First, a HEPES aqueous solution with a concentration of 10 mM was prepared with ultrapure water, and then the pH was adjusted to 6.8 with 1.0 M NaOH to obtain a 10 mM HEPES-NaOH (pH = 6.8) buffer solution. The gold-copper nanocluster powder obtained in Example 3 was placed in a HEPES-NaOH buffer with a pH of 6.8 to a concentration of 0.50 mg·L -1 a gold-copper nanocluster solution; then, an aqueous cerium nitrate solution with a concentration of 100 mM was prepared using ultrapure water, and the aqueous cerium nitrate solution was gradually dropped into the gold-copper nanocluster solution to make the final concentrations of cerium nitrate be 50, 100, 150, 200, 300, and 400 μM, respectively, and the fluorescence changes were monitored using fluorescence spectroscopy (excitation wavelength 370 nm).

[0044] The results show that Ce 3+ After the introduction of AuCu nanoclusters, the fluorescence intensity was enhanced, and along with Ce 3+ The fluorescence emission wavelength blue-shifted to 590 nm with the increase of Ce concentration. 3+ When the concentration reaches 200 μM, the Figure 4 ), 0.50 mg·L -1 Gold-copper nanoclusters with 200 μM Ce 3+ The AuCuNCs-Ce 3+ ), namely, the gold-copper nanoclusters and Ce based on glutathione protection described in the present invention 3+ Fluorescent probe solution of the assembly.

[0045] Embodiment 5:

[0046] The assembly obtained in Example 4 was placed in a refrigerator at 4°C, and its stability was monitored using a fluorescence spectrometer.

[0047] The results showed that the fluorescence spectrum of the assembly remained essentially unchanged within 25 days ( Figure 5 ), its stability is further improved, so the assembly can be used as a relatively stable fluorescent probe.

[0048] Embodiment 6:

[0049] The AuCuNCs-Ce 3+ The assembly is used as a stable fluorescent probe, and an acetone solution of myricetin is added to the assembly to make the final concentration of myricetin be 50 μM. The response speed of the assembly to myricetin is monitored by fluorescence spectroscopy (excitation 370 nm, emission 590 nm, time is minutes). In addition, the response range of the assembly to myricetin is tested, and a 10 mM myricetin solution is first prepared with acetone, and the 10 mM myricetin solution is gradually added dropwise to the assembly. At the same time, in order to test the detection limit of myricetin by the assembly, the fluorescent probe is diluted 10 times with a buffer solution, and then the myricetin solution (1 mM) is diluted in the same proportion, and the 1 mM myricetin solution is gradually added dropwise to the assembly after dilution, and the fluorescence intensity change at 590 nm is monitored by fluorescence spectroscopy.

[0050] The results showed that myricetin made AuCuNCs-Ce 3+ The assembly is quenched and responds quickly ( Figure 6 ). As the concentration of myricetin increases, the fluorescence intensity of the fluorescent probe at 590nm decreases, and finally reaches saturation when the concentration of myricetin is 300μM. Therefore, the response range to myricetin is between 0 and 300μM (Figure 7). In the detection limit test, there is a good linear relationship when the concentration of myricetin is 1.0 to 7.0μM. The linear relationship between the fluorescence intensity value at 590nm and the myricetin concentration is plotted, and the detection limit of myricetin is calculated to be 0.14 μM ( Figure 8 ).

[0051] Embodiment 7:

[0052] In order to study the AuCuNCs-Ce 3+ The selectivity of the assembly for myricetin was tested by using DMSO to prepare 10 mM apigenin, quercetin, and morin solutions and ultrapure water to prepare 10 mM solutions of 20 natural amino acids (Val, Met, Cys, Ile, Pro, Arg, Phe, Gly, Gln, Glu, Thr, Trp, Ser, Ala, Asp, Lys, Leu, Asn, Tyr, His). Then, apigenin solution, quercetin solution, morin solution, myricetin solution, and 20 natural amino acid solutions were added to the assembly, respectively, so that the final concentrations of apigenin, quercetin, morin, myricetin, and 20 natural amino acids were all 300 μM. All fluorescence tests were performed at room temperature, and then fluorescence spectroscopy tests were performed. In the test of AuCuNCs-Ce 3+ The interference of the assembly to myricetin, AuCuNCs-Ce 3+The assembly was placed in a HEPES-NaOH (pH 6.8) buffer solution, and after adding myricetin at a final concentration of 300 μM, a series of interfering substances (Val, Met, Cys, Ile, Pro, Arg, Phe, Gly, Gln, Glu, Thr, Trp, Ser, Ala, Asp, Lys, Leu, Asn, Tyr, His) were added respectively. The final concentration of each interfering substance added was 300 μM, and the fluorescence intensity change at 590 nm was monitored by fluorescence spectroscopy.

[0053] The results showed that in the selective experiment, apigenin, quercetin, and morin had a poorer fluorescence quenching effect than myricetin, and other substances (20 natural amino acids) had no effect on AuCuNCs-Ce 3+ The assembly has an effect ( Fig. 9 ), indicating that the fluorescent probe can effectively detect myricetin. In the interference test, the addition of other interfering substances to the solution containing myricetin did not affect the AuCuNCs-Ce 3+ Fluorescence response of the assembly to myricetin ( Fig.10 ). Therefore, we believe that these amino acids have an important effect on the fluorescent AuCuNCs-Ce 3+ The assembly probe had no effect on the detection of myricetin, indicating that this method is an effective means of detecting myricetin in practical applications.

[0054] Embodiment 8:

[0055] In order to explore the effect of myricetin on AuCuNCs-Ce 3+ The quenching mechanism of the assembly was first measured. 3+ The fluorescence lifetime of the assembly before and after the addition of myricetin. The excitation spectrum of the assembly and the ultraviolet absorption of myricetin were tested by a fluorescence spectrometer to compare whether the spectra overlap.

[0056] The results showed that AuCuNCs-Ce 3+ The average fluorescence lifetime of the assembly was 14.5106 ns. After adding myricetin, the average lifetime changed to 13.7623 ns (Table 1). The average fluorescence lifetime remained basically unchanged before and after the addition of myricetin, indicating that myricetin has an important effect on the AuCuNCs-Ce 3+ The maximum absorption peak of myricetin is close to that of AuCuNCs-Ce 3+ The excitation spectra of the assemblies overlap ( Fig.11). The inner filter effect occurs when the excitation spectrum of the fluorescent material has a significant overlap with the absorption spectrum of the quencher or analyte. Therefore, the inner filter effect may be the reason why myricetin makes AuCuNCs-Ce 3+ The overall results show that AuCuNCs-Ce 3+ The fluorescence quenching of the assembly can be attributed to the inner filter effect and is a static quenching process.

[0057] It should also be noted that the specific embodiments of the present invention are only used for illustrative purposes and do not limit the scope of protection of the present invention in any way. Relevant technicians in this field can make improvements or changes based on some of the above descriptions, but all these improvements and changes should fall within the scope of protection of the claims of the present invention.

Claims

1. A Glutathione-protected Au-Cu nanoclusters and Ce 3+ The application of the assembled fluorescent probe as a reagent in the detection of myricetin is characterized by: The fluorescent probe is prepared by the following steps: (1) First, 5.0 mL of 160-170 mM glutathione aqueous solution was added to 5.0 mL of 8-12 mM CuSO4∙5H2O aqueous solution. After the solution became a white suspension, 1.0 M NaOH aqueous solution was added dropwise to adjust the pH of the solution to 4.0-5.

0. The solution was then stirred at room temperature for 1.5-3.0 h to obtain a copper nanocluster solution. (2) adding HAuCl4∙3H2O to the copper nanocluster solution obtained in step (1) and stirring for 2 to 4 hours, wherein the final concentration of HAuCl4∙3H2O is 1.0 to 1.5 mM, to obtain a gold-copper nanocluster solution; (3) adding 15-30 mL of ethanol to the gold-copper nanocluster solution obtained in step (2), and then centrifuging at 6000-8000 rpm for 10-20 minutes to collect the precipitate; dissolving the precipitate in distilled water, adding ethanol and centrifuging 3-5 times to remove all residual small molecules, and lyophilizing to obtain pure gold-copper nanocluster powder; (4) The pure gold-copper nanocluster powder obtained in step (3) was placed in a 10 mM HEPES-NaOH buffer solution with a pH of 6.5-7.0 to prepare a gold-copper nanocluster concentration of 0.4-0.6 mg∙L -1 Then, an aqueous solution of cerium nitrate was added thereto for 10 to 30 minutes, and the final concentration of cerium nitrate was 100 to 300 μM, thereby obtaining a glutathione-protected gold-copper nanocluster and Ce nanoparticles. 3+ A fluorescent probe solution is formed to form an assembly.